2015
DOI: 10.1142/s0218271815300153
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational anomalies in the solar system?

Abstract: Mindful of the anomalous perihelion precession of Mercury discovered by U. Le Verrier in the second half of the nineteenth century and its successful explanation by A. Einstein with his General Theory of Relativity in the early years of the twentieth century, discrepancies among observed effects in our Solar system and their theoretical predictions on the basis of the currently accepted laws of gravitation applied to known matter-energy distributions have the potential of paving the way for remarkable advances… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 264 publications
(335 reference statements)
4
85
0
1
Order By: Relevance
“…This section is devoted to estimate the upper bound onν in the Solar System from the Laplace-Runge-Lenz (LRL) vector dynamics using the perihelion precession data from [70], which is more recent and precise than the data set used in [53].…”
Section: B Lrl Vector Dynamics With and Without The External Potentimentioning
confidence: 99%
“…This section is devoted to estimate the upper bound onν in the Solar System from the Laplace-Runge-Lenz (LRL) vector dynamics using the perihelion precession data from [70], which is more recent and precise than the data set used in [53].…”
Section: B Lrl Vector Dynamics With and Without The External Potentimentioning
confidence: 99%
“…Thus far, it was found that the cosmological constant Λ contributes to the perihelion shift in principle even though this contribution is presently difficult to detect because of its very small effect (See [6][7][8] and the references therein, and corresponding topic to perihelion advance [9][10][11][12]). …”
Section: Introductionmentioning
confidence: 99%
“…The extra perihelion precessions of the planets (from Mercury to Saturn) in the Solar system estimated from the recent ephemerides INPOP10a [62] and EPM2011 [63] (see also [36]) are listed in Table 1.…”
Section: Perihelion Precessionmentioning
confidence: 99%
“…On the other hand, any modified gravity theory must confront the Solar system tests which have been passed in GR [33][34][35][36][37]. In fact, Solar system effects in some modified gravities including minimal coupling f (T ) models have been considered [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%